2022
DOI: 10.1002/adem.202101562
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Downfacing Surfaces in Selective Laser Melting

Abstract: This article presents an investigative study to evaluate the effect of process parameters on surface roughness and dimensional accuracy of downfacing surfaces. The material used in the study is Corrax steel and is fabricated using selective laser melting (SLM) technology. The fabrication process of the downfacing surface is different from the fabrication of the main or core region due to the poor thermal conductivity of loose powder particles beneath each layer. The processing parameters, namely, laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is also possible to influence the surface quality by changing the technological parameters, among which the laser power [24], the scanning speed of the laser spot [25], the hatch distance parameter, the layer thickness [26] and the scanning strategy are also defined as important parameters [27]. It has been shown that the specific energy density used producing of the components' contours also affects the surface's quality [28]. In the case of aluminium raw materials, it was shown that a low surface roughness value requires a slow scanning speed and a small hatching distance.…”
Section: Articlementioning
confidence: 99%
“…It is also possible to influence the surface quality by changing the technological parameters, among which the laser power [24], the scanning speed of the laser spot [25], the hatch distance parameter, the layer thickness [26] and the scanning strategy are also defined as important parameters [27]. It has been shown that the specific energy density used producing of the components' contours also affects the surface's quality [28]. In the case of aluminium raw materials, it was shown that a low surface roughness value requires a slow scanning speed and a small hatching distance.…”
Section: Articlementioning
confidence: 99%
“…[13,14] However, they introduce drawbacks, such as poor surface quality, prolonged build times, and the need for labor-intensive postprocessing to remove the support structures, adding to production costs. [9,15] Topology optimization studies are conducted to determine the optimal material required in support structures. These optimized support structures effectively minimize part deflection during the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%